Understanding Childhood Neuroimmune Diseases of the Central Nervous System - Matricardi, Sara; Farello, Giovanni; Savasta, Salvatore; Verrotti, Alberto (Frontiers in Pediatrics, 2019)
Immune-mediated diseases of the central nervous system (CNS) in childhood are a heterogeneous group of rare conditions sharing the inflammatory involvement of the CNS. This review highlights the growing knowledge of childhood neuroimmune diseases that primarily affect the CNS, outlining the clinical and diagnostic features, the pathobiological mechanisms and genetics, current treatment options, and emerging challenges. The clinical spectrum of these conditions is increasingly expanded, and the underlying mechanisms of dysregulation of the immune system could vary widely. Cell-mediated and antibodies-mediated disorders, infection-triggered, paraneoplastic conditions, and genetically defined mechanisms can occur in previously healthy children and can contribute to different stages of the disease. The careful evaluation of the clinical presentation and temporal course of symptoms, the specific neuroimaging and immunological findings, and the exclusion of alternative causes are mandatory in clinical practice for the syndromic diagnosis. A common feature of these conditions is that immunotherapeutic agents could modulate the clinical course and outcomes of the disease. Furthermore, specific symptomatic treatments and comprehensive multidisciplinary care are needed in the overall management. We focus on recent advances on immune-mediated demyelinating CNS disorders, autoimmune encephalitis, interferonopathies, and possible neuroimmune disorders as Rasmussen encephalitis. Better knowledge of these conditions could allow prompt diagnosis and targeted immunotherapy, to decrease morbidity and mortality, as well as to improve clinical outcomes reducing the burden of the disease due to possible long-term neuropsychiatric sequelae. Persisting controversies remain in the rigorous characterization of each specific clinical entity because of the relative rarity in children; moreover, in a large proportion of suspected neuroimmune diseases, the immune “signature” remains unidentified; treatment guidelines are mostly based on retrospective cohort studies and expert opinions, then advances in specific molecular therapies are required. In the future, a better characterization of specific immunological biomarkers may provide a useful understanding of the underlying pathobiological mechanisms of these conditions in order to individualize more tailored therapeutic options and paradigms. Multicenter collaborative research on homogeneous groups of patients that may undergo immunological studies and therapeutic trials could improve the characterization of the underlying mechanisms, the specific phenotypes, and tailored management.